Derivation and investigation of the first human cell-based model of Beckwith-Wiedemann syndrome. Issue 12 (2nd December 2021) - Chang, Suhee; Hur, Stella K.; Naveh, Natali S. Sobel; Thorvaldsen, Joanne L.; French, Deborah L.; Gagne, Alyssa L; Jobaliya, Chintan D.; Anguera, Montserrat C.; Bartolomei, Marisa S.; Kalish, Jennifer M
ABSTRACT: Genomic imprinting is a rare form of gene expression in mammals in which a small number of genes are expressed in a parent-of-origin-specific manner. The aetiology of human imprinting disorders is diverse and includes chromosomal abnormalities, mutations, and epigenetic dysregulation of imprinted genes. The most common human imprinting disorder is Beckwith-Wiedemann syndrome (BWS), frequently caused by uniparental isodisomy and DNA methylation alterations. Because these lesions cannot be easily engineered, induced pluripotent stem cells (iPSC) are a compelling alternative. Here, we describe the first iPSC model derived from patients with BWS. Due to the mosaic nature of BWS patients, both BWS and non-BWS iPSC lines were derived from the same patient's fibroblasts. Importantly, we determine that DNA methylation and gene expression patterns of the imprinted region in the iPSC lines reflect the parental cells and are stable over time. Additionally, we demonstrate that differential expression in insulin signalling, cell proliferation, and cell cycle pathways was seen in hepatocyte lineages derived from BWS lines compared to controls. Thus, this cell based-model can be used to investigate the role of imprinting in the pathogenesis of BWS in disease-relevant cell types.